Antioxidant Activity Test of Ethanol Extract of Sarcophyton sp. Obtained at Parentek Beach, Minahasa Regency - Berlian Tasya Tumundo; Adithya Yudistira; Erladys Melindah Rumondor (UNIVERSITAS SAM RATULANGI, 2024)
Sarcophyton sp. contain bioactive compounds that are efficacious as antioxidants. The purpose of this research is to determine the antioxidant activity of ethanol extract produced by Sarcophyton sp. By extraction using maceration method with 95% ethanol solvent and testing using DPPH (1,1- diphenyl-2-picrylhydrazyl) method. The results of data analysis of % inhibition obtained were 47.09% (20 ppm), 54.8% (40 ppm), 56.7% (60 ppm), 60.6% (80 ppm) and 62.4% (100 ppm). The ethanol extract of Sarcophyton sp. obtained from Parentek Beach, Minahasa Regency has the highest antioxidant activity at a concentration of 100 ppm which is 62.4%..